Quantum‐based Modeling of Protein‐ligand Interaction: The Complex of RutA with Uracil and Molecular Oxygen. Issue 2 (4th November 2022) - Polyakov, Igor V.; Nemukhin, Alexander V.; Domratcheva, Tatiana M.; Kulakova, Anna M.; Grigorenko, Bella L.
Abstract: Modern quantum‐based methods are employed to model interaction of the flavin‐dependent enzyme RutA with the uracil and oxygen molecules. This complex presents the structure of reactants for the chain of chemical reactions of monooxygenation in the enzyme active site, which is important in drug metabolism. In this case, application of quantum‐based approaches is an essential issue, unlike conventional modeling of protein‐ligand interaction with force fields using molecular mechanics and classical molecular dynamics methods. We focus on two difficult problems to characterize the structure of reactants in the RutA‐FMN‐O2 ‐uracil complex, where FMN stands for the flavin mononucleotide species. First, location of a small O2 molecule in the triplet spin state in the protein cavities is required. Second, positions of both ligands, O2 and uracil, must be specified in the active site with a comparable accuracy. We show that the methods of molecular dynamics with the interaction potentials of quantum mechanics/molecular mechanics theory (QM/MM MD) allow us to characterize this complex and, in addition, to surmise possible reaction mechanism of uracil oxygenation by RutA. Abstract :